INFLUENCE OF CULTURE MEDIUM ON THE SPORULATION AND VIABILITY OF ASPERGILLUS SPP. AND TALAROMYCES SPP. ENTOMOPATHOGENIC FUNGI - Fitriana, Yuyun; Suharjo, Radix; Swibawa, I Gede; ., Purnomo; Lestari, Puji; Merdiana, Eryka (Universitas Lampung, 2018)
Influence of Culture Medium on the Sporulation and Viability of Aspergillus spp. and Talaromyces spp. Entomopathogenic Fungi. The purpose of this study was to determine the effect of three kinds of cultures media on the spore production and viability of Aspergillus spp. (AS1, 6, 7, 9) and Talaromyces spp. (AS2?5, 8, 10) entomopathogenic fungi. This study was arranged using Factorial-Completely Randomized Design (CRD) with 2 factors and 3 replications. The first factor was three kinds of cultures media (potato dextrose agar (PDA), corn meal agar (CMA), and sabouraud dextrose agar (SDA)) and the second one was isolates of Aspergillus spp. Or Talaromyces spp.. Data of spore production and spore viability were tested using ANOVA and if there was significantly difference, the data then further analyzed using Tukey?s Honestly Significant Difference (HSD) test at 5% of significant level. The spore production of Aspergillus spp. were in the range of 0.58 - 14.27 x 108 spores mL-1 (PDA); 0.28 ? 2.68 x 108 spores mL-1 (SDA) and 1.85 - 5.33 x 108 spores mL-1 (CMA). The highest spore production was achieved by AS1 isolate that was grown on PDA media. The spore produced by Talaromyces spp. were in the range of 2.15 ? 28.62 x108 spores mL-1 (PDA); 0.28 ? 29.43 x108 spores mL-1 (SDA); and 1.88 ? 16.63 x108 spores mL-1 (CMA). The highest spore production was produced by AS8 isolate which were cultured on PDA. The spore viability among isolates of the two entomopathogenic fungi were not significantly different. The spore viability of Aspergillus spp. was in the range of 95.10 ? 97.66% (PDA), 94.02 ? 98.45% (SDA) and 92.86 ? 98.20% (CMA). The spore viability of Talaromyces spp. was in the range of 95.83 ? 100% (PDA), 85.83 ? 100% (SDA), and 90.75 ? 100% (CMA). Culture medium influenced spore production but not the spore viability. The best culture media used for spore production of both of the entomopathogenic fungi was PDA media.